Analisis Avability Infrastruktur Jaringan VOIP di Universitas Sahid Surakarta - Susilo, Dahlan; Saputro Al Haris, Firdhaus Hari; Wahono, Ari (Gaung Informatika, 2011)
VoIP  is a technology  that utilizes  the Internet  Protocol  to  provide  voice communications electronically and in real-time. How it works to change the voice into digital data format that can be transmitted through a specific IP network. Conducted research methodology, consisting of six strands include observational studies and interviews, literature study, analysis and system design, experiment, test the quality of the system, and conclusions. VoIP works on a computer network  installed VoIP server. The server acts as a proxy  that has  the benefits of  inter-user communication. VoIP communications can be carried out within  the scope of the  campus  and outside the  campus with  an internet connection. The test results  with  the  method of  random sampling  McCall  using  several factors  related to the operational properties of  software,  it can be concluded  that the quality of VoIP in Sahid University of Surakarta was 76.5% with good results.